Poésie de la langue des colonies dans Nos Créoles d’Armand Corre (1890) - Odile Hamot (Études Caribéennes)
The aim of this article is to show how the reflection on the Creole language put forward by Armand Corre, a Navy doctor, in the ‘political-sociological’ study he published in 1890 under the title Nos Créoles, is nourished by anthropological biases that are clearly stated or perceptible in the background, and results in an astonishing axiological inversion: to the inadequacies of a negro language seen through the blinkers of an epochal racism as the language of ‘big children’ are added the seductions of a language-woman, rich in all the exotic imaginary aroused by the white Creole and mulatto woman since the 18th century, as well as the idealizing nostalgia for a lost original world that finds its source in literature. This idealized past, perceived as the childhood of the social world, ultimately anchors the Creole language in the space of poetry. Only in this way does Creole society find favor in Armand Corre’s eyes.